Synthesis and characterization of the Co(ii), Ni(ii), and Cu(ii) complexes with a 1,2,4-triazine derivative ligand - Althubeiti Khaled (Open Chemistry, 2025)
This study focuses on synthesizing a 1,2,4-triazine derivative, 5-(5-bromo-2-hydroxybenzylidene)-6-oxo-3-phenyl-5,6-dihydro-1,2,4-triazine-2(1H)-carbothio-amide (termed as HL), and the subsequent use of this ligand to capture three metal ions: Co(ii), Ni(ii), and Cu(ii). The objectives included the synthesis of the ligand from 5-bromosalicylaldehyde and hippuric acid; the preparation of its metal complexes with the three transition metal ions; the verification of complexation stoichiometry using CHN and gravimetric analysis; the characterization of the ligand and complexes via spectroscopic techniques; the determination and comparison of their thermal properties through thermogravimetric (DTG) measurements; and the examination and comparison of their microstructures using powder X-ray diffraction (XRD) and transmission electron microscopy (TEM). Spectral, elemental, conductivity, and thermal data suggest general compositions of [CoL(H2O)4]‧Cl·6H2O for the Co(ii) complex, [NiL(H2O)4]·Cl·4H2O for the Ni(ii) complex, and [CuL(H2O)Cl]·2H2O for the Cu(ii) complex. TEM images revealed that the initially rod-like morphology of the ligand particles transformed into a stone-like appearance upon coordination with the Co(ii), Ni(ii), and Cu(ii) ions. Finally, the antibacterial activity of the synthesized complexes was evaluated against five microbial strains to assess the impact of complexation on the antibacterial profile of the free ligand. The screening data indicated that the complexes exhibited improved antibacterial potency compared to the free ligand.